The Nontraditional Quality of Organizational Learning - Weick, Karl E. (Organization Science, 1991)
The traditional definition of learning as a shift in performance when the stimulus situation remains essentially the same implies a set of conditions that occur rarely in organizations. Thus, either organizational learning is an infrequent event, or it occurs frequently but takes a nontraditional form. Both possibilities are reviewed and implications for research strategy are suggested.